Biosafety and biosecurity challenges during the COVID-19 pandemic and beyond - Rutjes, Saskia A.; Vennis, Iris M.; Wagner, Edith; Maisaia, Vakhtang; Peintner, Lukas (Frontiers in Bioengineering and Biotechnology, 2023)
As the world continues to battle the SARS-CoV-2 pandemic, it is a stark reminder of the devastation biological threats can cause. In an unprecedented way the global community saw a massive surge in the demand for diagnostic capacities, which had a substantial impact on biosafety and biosecurity. Laboratories had to cope with a surge in laboratory testing capacity, while resources and training possibilities were limited. In addition, the pandemic highlighted the impact biological threats can have, thereby giving rise to new dialogue about biosecurity and new biological threats. This paper aims to highlight some of the most pressing issues regarding biosafety and biosecurity observed during the COVID-19 pandemic with special focus on low and lower middle-income countries. The authors provide lessons learned, tools and recommendations to improve future biosafety and biosecurity and increase preparedness for the next global health crisis.